How Do Teacher and Students Interact and Communicate during The Instructional Process in The Classroom? - Ridhayani Ridhayani (Universitas Syiah Kuala, 2018)
This qualitative study is designed with the aim to investigate the teacher and students’ interpersonal communication skill, their interaction in the classroom along with their difficulties. The study focused on thirty five senior EFL students in an English class of Oemar Diyan Islamic Boarding School. Data collection was conducted by observing a teacher and the students during the instructional process using the format of observation sheet from Markovic and Axmann (2007) and British Columbia Institute of Technology; Instructional Job Aid | Developing Checklists and Rating Scales). In addition, a semi-structured interview to a teacher and five students were also conducted to investigate their difficulties in communicating and interacting during the instructional process in the classroom. The findings indicated that the teacher and students still have lack of communication and interaction. The teacher and students experienced many difficulties in communicating and interacting with each other during the instructional process. Most of the students’ difficulties are the drowsiness and friend distraction. The students often feel very exhausted when learning and they become sleepy and careless to the teacher’s teaching. Besides, students also experienced friend distraction when they are trying hard to focus and respond to their teacher. In another way, the teacher feels overwhelmed to control many students in one classroom. It becomes the teacher’s most difficulty to engage the students in a dialog to build a communication and interaction in one meeting.